Defining a core microbial necrobiome associated with decomposing fungal necromass - Cantoran, Anahi; Maillard, François; Baldrian, Petr; Kennedy, Peter G (FEMS microbiology ecology, 2023)
Despite growing interest in fungal necromass decomposition due to its importance in soil carbon retention, whether a consistent group of microorganisms is associated with decomposing necromass remains unresolved. Here, we synthesize knowledge on the composition of the bacterial and fungal communities present on decomposing fungal necromass from a variety of fungal species, geographic locations, habitats, and incubation times. We found that there is a core group of both bacterial and fungal genera (i.e. a core fungal necrobiome), although the specific size of the core depended on definition. Based on a metric that included both microbial frequency and abundance, we demonstrate that the core is taxonomically and functionally diverse, including bacterial copiotrophs and oligotrophs as well as fungal saprotrophs, ectomycorrhizal fungi, and both fungal and animal parasites. We also show that the composition of the core necrobiome is notably dynamic over time, with many core bacterial and fungal genera having specific associations with the early, middle, or late stages of necromass decomposition. While this study establishes the existence of a core fungal necrobiome, we advocate that profiling the composition of fungal necromass decomposer communities in tropical environments and other terrestrial biomes beyond forests is needed to fill key knowledge gaps regarding the global nature of the fungal necrobiome.
Keywords: Mycobiome; lesy; mykobiom; core microbiome; Carbon; necromass soil organic matter; Animals; Mycorrhizae; uhlík; mykorhiza; bacteria; fungi; zvířata; Forests; decomposition; ekosystém; Ecosystem